2022
DOI: 10.21303/2461-4262.2022.002523
|View full text |Cite
|
Sign up to set email alerts
|

Research and modeling of oil refining technological processes operating in the condition of stochastic uncertainty

Abstract: As it is known, one of the initial and important stages in the creation of optimal control systems of oil refining technological units is the development of a mathematical model that can adequately record the processes at any time. The operative and accurate measurement of all input and output variables is one of the important conditions in the development of a mathematical model of technological processes. Studies have shown that the lack of information about the state of complex oil refining proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The experience of operating the optimal control systems of complex petrochemical and oil refining technological processes showed that the lack of information on the course of processes in many cases reduces their efficiency and productivity. On the other hand, the change in a wide range of quality indicators and consumption of raw materials for processing makes their efficiency even more unsatisfactory [1]. In some cases, this is due to the nonlinear and non-stationary dynamic characteristics of these systems [2].…”
Section: Introductionmentioning
confidence: 99%
“…The experience of operating the optimal control systems of complex petrochemical and oil refining technological processes showed that the lack of information on the course of processes in many cases reduces their efficiency and productivity. On the other hand, the change in a wide range of quality indicators and consumption of raw materials for processing makes their efficiency even more unsatisfactory [1]. In some cases, this is due to the nonlinear and non-stationary dynamic characteristics of these systems [2].…”
Section: Introductionmentioning
confidence: 99%